The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-2621.2009.01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of twenty‐one Caribbean sweet potato cultivars

Abstract: The physical, chemical and physicochemical properties of twenty-one Caribbean sweet potato cultivars were investigated. Hunter L a b colour parameters were measured, chroma, colour intensity and hue angle were calculated. Proximate composition, vitamin C, amylose, reducing and non-reducing sugars contents were determined using standard methods. Pasting properties were determined using Rapid Visco Analyser. Tuber size (length, r = 0.72, n = 21, P < 0.0015; width, r = 0.85, n = 21, P < 0.0002) was highly correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
95
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(121 citation statements)
references
References 31 publications
18
95
5
1
Order By: Relevance
“…Consumers enjoy the pleasant odor and flavor of baked sweet potatoes. Although chemical composition analysis of sweet potatoes has been previously documented (Ahmed et al 2010;Ahromrit and Nema 2010;Aina et al 2009;Picha 1985;Picha 1986;Vimala et al 2011), little information on the effect of baking has been reported (Lai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers enjoy the pleasant odor and flavor of baked sweet potatoes. Although chemical composition analysis of sweet potatoes has been previously documented (Ahmed et al 2010;Ahromrit and Nema 2010;Aina et al 2009;Picha 1985;Picha 1986;Vimala et al 2011), little information on the effect of baking has been reported (Lai et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is the major carbohydrate found in sweet potatoes, and comprises approximately 20 % of the fresh tuber (Aina et al 2009). Baking breaks down starch granules to form disaccharides and monosaccharides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kure [39] reported that the pH value of seven sweet potato varieties was ranged from 5.5 to 7.1. Aina and Woolfe et al [40,41] reported that the range of pH in sweet potato varieties were ranged from 5 to 6.9 and 5.5 to 6.7. These findings are strongly agreed with the present findings.…”
Section: Percentage (%)mentioning
confidence: 99%
“…Protein content is 1% to 2% and it has high biological value due to its high lysine content, whereas lipid level is reduced (0.1 to 0.4%) (Mazzei et al, 1995;FAO, 2002). Other minor components in sweet potato are vitamins, pigments and antioxidant compounds (β-carotene, vitamin B, C, E, phenolic acid) (Martí, 2000;Aina et al, 2009;Picha and Padda, 2009) being good energy providers as well, 111 kcal/100g (Martí, 2000). Moreover, Miyazaki et al (2005) reported that the consumption of white skinned sweet potatoes is an effective alternative to the prevention and improvement of the symptoms of diabetes because it stimulates human immunity.…”
Section: Introductionmentioning
confidence: 99%